Auto‐Tandem Catalysis‐Induced Synthesis of Trisubstituted Furans through Domino Acid‐Acid‐Catalyzed Reaction of Aliphatic Aldehydes and 1, 3‐Dicarbonyl Compounds by using N‐Bromosuccinimide as Oxidant. Issue 11 (15th March 2017) - Huang, Wenbo; Liu, Changhui; Gu, Yanlong
Abstract: A simple aluminium(III) chloride‐catalyzed synthesis of tri‐substituted furans from aliphatic aldehydes and 1, 3‐dicarbonyl compounds was developed by using N ‐bromosuccinimide (NBS) as an oxidant. This method was effective for the synthesis of various furan derivatives. Some of the products were not accessible with the previously reported methods. Mechanically, this reaction involved an auto‐tandem catalysis based on a newly reported acid‐acid‐catalyzed tandem reaction to ensure that furans were successfully synthesized. Abstract :